# final2 - Granillo Yvette – Final 1 – Due 10:00 pm –...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Granillo, Yvette – Final 1 – Due: May 10 2006, 10:00 pm – Inst: E Schultz 1 This print-out should have 25 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. The due time is Central time. 001 (part 1 of 1) 10 points Find the derivative of f ( t ) = ln t 3- ln t . 1. f ( t ) = 3 ln t (3- ln t ) 2 2. f ( t ) = t (3- ln t ) 2 3. f ( t ) = t (3- ln t ) 2 4. f ( t ) = 3 ln t 3- ln t 5. f ( t ) = 3 t (3- ln t ) 2 correct 6. f ( t ) = ln t 3- ln t Explanation: By the Quotient Rule, f ( t ) = (3- ln t )(1 /t ) + (ln t )(1 /t ) (3- ln t ) 2 . Consequently, f ( t ) = 3 t (3- ln t ) 2 . keywords: Stewart5e, derivative, Quotient Rule, log function, 002 (part 1 of 1) 10 points Find the derivative of f when f ( x ) = 7 x cos 3 x- 4 sin 3 x. 1. f ( x ) =- 12 cos 3 x + 21 x sin 3 x 2. f ( x ) = 12 cos 3 x- 5 x sin 3 x 3. f ( x ) =- 21 x sin 3 x- 5 cos 3 x correct 4. f ( x ) =- 21 x sin 3 x- 12 cos 3 x 5. f ( x ) = 21 x sin 3 x- 5 cos 3 x Explanation: Using formulas for the derivatives of sine and cosine together with the Product and Chain Rules, we see that f ( x ) = 7 cos 3 x- 21 x sin 3 x- 12 cos 3 x =- 21 x sin 3 x- 5 cos 3 x . keywords: Stewart5e, 003 (part 1 of 1) 10 points Determine f ( x ) when f ( x ) = cos( e- x ) . 1. f ( x ) = e- x sin( e- x ) correct 2. f ( x ) = e- x cos( e- x ) 3. f ( x ) =- e- x sin( e- x ) 4. f ( x ) =- cos( e- x )- e- x 5. f ( x ) =- sin( e- x ) 6. f ( x ) = cos( e- x ) + e- x Explanation: By the Chain Rule, f ( x ) = sin( e- x ) d dx e- x . Consequently, f ( x ) = e- x sin( e- x ) . Granillo, Yvette – Final 1 – Due: May 10 2006, 10:00 pm – Inst: E Schultz 2 keywords: Stewart5e, 004 (part 1 of 1) 10 points Find the derivative of f when f ( x ) = ln s 1 + 2 x 2 1- 2 x 2 . 1. f ( x ) = 4 x 1- 4 x 4 correct 2. f ( x ) = 2 x 1- 2 x 4 3. f ( x ) = 4 x 1- 2 x 4 4. f ( x ) =- 2 x 1- 4 x 4 5. f ( x ) =- 4 x 1- 4 x 4 6. f ( x ) =- 4 x 1- 2 x 4 7. f ( x ) = 2 x 1- 4 x 4 8. f ( x ) =- 2 x 1- 2 x 4 Explanation: Properties of logs ensure that ln s 1 + 2 x 2 1- 2 x 2 = 1 2 n ln(1 + 2 x 2 )- ln(1- 2 x 2 ) o . By the Chain rule, therefore, f ( x ) = 1 2 n 4 x 1 + 2 x 2 + 4 x 1- 2 x 2 o . Consequently, f ( x ) = 4 x 1- 4 x 4 . keywords: Stewart5e, 005 (part 1 of 1) 10 points Find the derivative of f when f ( x ) = 4 tan- 1 ( e 3 x ) . 1. f ( x ) = 4 1 + e 3 x 2. f ( x ) = 3 e 3 x 1 + e 3 x 3. f ( x ) = 4 9 + e 6 x 4. f ( x ) = 3 e 3 x 9 + e 6 x 5. f ( x ) = 12 e 3 x 1 + e 6 x correct 6. f ( x ) = 12 e 3 x 9 + e 3 x Explanation: By the Chain Rule, f ( x ) = 3 · 4 e 3 x 1 + e 6 x since d dx tan- 1 x = 1 1 + x 2 , ( e 3 x ) 2 = e 6 x . Consequently, f ( x ) = 12 e 3 x 1 + e 6 x ....
View Full Document

## This test prep was uploaded on 04/16/2008 for the course M 408k taught by Professor Schultz during the Spring '08 term at University of Texas.

### Page1 / 13

final2 - Granillo Yvette – Final 1 – Due 10:00 pm –...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online